Tuina alleviates the muscle atrophy induced by sciatic nerve injury in rats through regulation of PI3K/Akt signaling - Yingqi Zhang; Hanyu Zhang; Jiayue Liu; Jiawei Sun; Yue Xu; Narentuya Shi; Hongzheng Zhang; Jiawang Yan; Jinping Chen; Hourong Wang; Tianyuan Yu (Journal of Orthopaedic Surgery and Research)
Abstract Background Tuina is an effective treatment for the decrease of skeletal muscle atrophy after peripheral nerve injury. However, the underlying mechanism of action remains unclear. This study aimed to explore the underlying mechanisms of tuina in rats with sciatic nerve injury (SNI). Methods We established an SNI rat model. After Tuina intervention, curative effects were evaluated by behavioral assessment, nerve function index, and muscle atrophy index (MAI). Pathological changes were observed by transmission electron microscopy and immunofluorescence. Insulin-like growth factor 1 (IGF-1), forkhead box O (FoxO) and p-FoxO levels were detected using enzyme-linked immunosorbent assay. Western blotting was performed to detect the expression of proteins involved in the PI3K/AKT signaling pathway. Result Behavioral assessment, nerve function index, and MAI revealed that the tuina had significantly improved muscle atrophy after SNI compared with the SNI model group. Transmission electron microscopy showed that tuina improved muscle ultramicrostructure. CD31 immunofluorescence revealed that tuina improved microcirculation. Furthermore, we observed that tuina differentially regulated the levels of IGF-1, FoxO and p-FoxO, and the protein expression of p-Phosphoinositide 3-kinase (p-PI3K), p-AKT, and vascular endothelial growth factor in the anterior tibial muscle and soleus muscles. Conclusion Tuina could effectively inhibit skeletal muscle atrophy via the microcirculation pathway in a rat model of SNI by regulating the expression of IGF-1 and FoxO. The underlying mechanism of action may involve the PI3K/Akt signaling pathway.